2008
DOI: 10.1103/physrevc.78.035803
|View full text |Cite
|
Sign up to set email alerts
|

AstrophysicalSfactor forαcapture onSn117

Abstract: The cross sections of the 117 Sn(α, γ ) 121 Te and 117 Sn(α, p) 120 Sb reactions have been measured in the effective center of mass energy from 11.5 to 14.6 MeV. Highly enriched self-supporting 117 Sn (90%) foils were bombarded with an α beam delivered by the Bucharest IFIN-HH tandem accelerator. The induced activity of 121 Te and 120 Sb was measured with two large-volume high-purity Ge detectors in close geometry to maximize the detector efficiency. The experimental cross section and astrophysical S factor ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 25 publications
(25 reference statements)
0
36
0
Order By: Relevance
“…This approach provides more relevant astrophysical information than the direct study of the γ -induced reactions since often the influence of thermally excited states is smaller in this direction, compared to photon-induced reactions [16,[22][23][24]. In recent years several α-capture cross sections have been measured using the well known activation technique [25][26][27][28][29][30][31][32][33], and the results were compared with the H-F predictions. In general, it was found that the H-F cross sections are very sensitive to the choice of the α + nucleus OMP, in particular at energies significantly below the Coulomb barrier, which is the most relevant energy range for the calculation of stellar reaction rates.…”
Section: A the Astrophysical γ Processmentioning
confidence: 99%
“…This approach provides more relevant astrophysical information than the direct study of the γ -induced reactions since often the influence of thermally excited states is smaller in this direction, compared to photon-induced reactions [16,[22][23][24]. In recent years several α-capture cross sections have been measured using the well known activation technique [25][26][27][28][29][30][31][32][33], and the results were compared with the H-F predictions. In general, it was found that the H-F cross sections are very sensitive to the choice of the α + nucleus OMP, in particular at energies significantly below the Coulomb barrier, which is the most relevant energy range for the calculation of stellar reaction rates.…”
Section: A the Astrophysical γ Processmentioning
confidence: 99%
“…In this direction the influence of thermally excited states remains relatively small [7,8]. In recent years a range of (α,γ ) reaction cross sections on 70 Ge, 96 Ru, 106 Cd, 112,117 Sn, 113 In, 144 Sm, 151 Eu, and 169 Tm has been measured using the activation method, and the results have been compared with model predictions [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of α-beam activation measurements have been conducted for targets relevant to pprocess [5][6][7][8][9][10][11][12][13]. Cross sections of the corresponding (α,x) reactions were measured at, or close to, the astrophysically relevant energy.…”
mentioning
confidence: 99%